Team teaching in early childhood : leadership tools for reflective practice - Carruyo, Uniit (St. Paul, MN : Redleaf Press, 2017)
Discover how to support high-functioning and collaborative teacher teams in early childhood programs by developing healthy and confident team leaders. This manual covers topics of dynamic team teaching including: how to create unified teams, how to become teacher leaders, how to give and receive feedback, and how to build and assess differentiated curriculum. Uniit Carruyo has been an early childhood educator for more than twenty years and is currently the Director of Education at Ithaca Montessori School in Ithaca, New York. Carruyo received her MS Ed in Leadership from Bank Street College of Education.
Foundations of team teaching -- Team roles in an early childhood setting -- Teamwork in action: communication strategies -- Foundational elements of an effective classroom team --Feedback -- Team meetings.
Includes bibliographical references : page 107 and index.
Keywords: Teaching teams -- United States; Early childhood education -- United States